Resilience and self-harm among left-behind children in Yunnan, China: a community-based survey - Xin Tian; Wei Chang; Qiong Meng; Ying Chen; Zhen Yu; Limei He; Yuanyuan Xiao (BMC, 2019)
Abstract Background Self-harm (SH) behaviors are established risk factors of suicide, however, in Chinese left-behind children (LBC), SH remains severely under-discussed. In this study, we aimed to investigate SH and explore its association between resilience in a large group of LBC. Methods A community-based cross-sectional study of 2898 LBC was conducted in Yunnan province, China. Information was collected by self-reporting questionnaires. Descriptive analysis was used to depict and compare characteristics of the subjects. Univariate and multivariate logistic regression models were applied to estimate the associations between resilience and SH prevalence, SH severity, SH repetition. Results The prevalence of SH in LBC was 48.8% (95%CI: 47.0-49.7%). Compared to LBC with lower level of resilience, a higher level of resilience was related to 0.40 folds of SH odds (95%CI: 0.34-0.48). Besides, among all dimensions of resilience, every 1 average score increase of emotion regulation and family support were associated with 0.13 (95%CI: 0.04-0.37) and 0.14 (95%CI: 0.04-0.47) folds of odds in severer SH, respectively; one unit increase in the average score of emotion regulation was related to an OR of 0.23 (95%CI: 0.07-0.71) for repeated SH. Conclusions Psychological resilience presented protective effect on SH in LBC, especially the dimensions of emotion regulation and family support. Intervention measures focusing on enhancing emotion regulation ability and building parent-child connection could be considered in order to reduce SH and suicidal risk in LBC.